Synthesis and VHDL Implementation of Fuzzy Logic Controller for Dynamic Voltage and Frequency Scaling (DVFS) Goals in Digital Processors - Pourshaghaghi, Hamid Reza; Escobar, Juan Diego Echeverri; Gyvez, José Pineda de (IntechOpen, 2012)
None